Application of a capacitance sensor for monitoring water lubricated pipeline flows. (7th August 2014) - Rushd, Sayeed; Sanders, R. Sean
<x xml:space="preserve">Abstract</x> Lubricated pipe flow (LPF) is a pipeline transportation technology for highly viscous oils. In this technology, a viscous oil‐core is lubricated by an enveloping water annulus. A major technical challenge for LPF is the flow instability caused by a fouling layer of viscous oil on pipe wall. To monitor the thickness of this layer, application of a capacitance sensor has been investigated. The experiments were conducted with two laboratory‐scale sensors: a bench‐top concentric pipe spool set‐up and a rectangular flow cell. The experimental study was complemented with simulations obtained using COMSOL Multiphysics. The results from these experimental and numerical studies are in good agreement. The current research suggests that capacitance sensors similar to the ones described here can be used to monitor the thickness of a wall‐fouling layer. This monitoring will facilitate the reliable operation of LPF pipelines.